Prevalência do antígeno de superfície do vírus da hepatite B, em municípios maranhenses - Silva, Camila Maria Pinheiro de Mello e (2015)
Hepatitis B is a serious public health problem, in course in most asymptomatic cases, making diagnosis often late and unfavorable prognosis to patients of Hepatitis B Virus (HBV). It presents the transmission mechanisms associated with percutaneous / parenteral, sexual, perinatal and intrafamily route. It shows a prevalence with a broad global and Brazilian distribution, and in the State of Maranhão, it is still underestimated, especially in remote municipalities of the capital, São Luis. This study aimed to investigate the prevalence of antigen of the Hepatitis B Virus Surface in Maranhão, in the municipalities of Urbano Santos and municipalities of the lower Munim region. The data were taken from the search database Study of Hepatitis B, C and D in the Municipalities of Urbano Santos and municipalities of the Lower Munim Region, Maranhão, Brazil. It was used a quantitative approach, cross-sectional epidemiological design, carried out from March 2012 to July 2015. The study included 3860 people aged at least one year, who lived in those cities for at least six months. The results showed a population aged 20-39 years (29.35%), average age 28, female majority (57.9%), single (33.22%) with primary education (60 40%), household income of less than one minimum salary (53.68%), most brown color (64.69%) and living in rural areas (63.32%). It was detected a prevalence for HBV 3.26% (n = 126), 39.7% (n = 50) lived in the city of Humberto de Campos, 21.4% (n = 27) in Urbano Santos, 19 8% (n = 25) in Hills, 15.1% (n = 19) Icatú and 4% (n = 5) Axixá. There was a higher prevalence of HBsAg in the higher age groups of 60-79, (7%); and 80-99 years (8%); regarding the gender, although the female population is bigger, there was a higher frequency of infected men between 1559 participants (66%). With regard to marital status those with no stable relationship (single, divorced or widowed) had the highest prevalence (14.53%) than those in stable relationships (married or common-law marriage) (9.42%). In addition, it was found also a population that uses needlestick materials, especially pliers 2067 (98.8%) and shaver in 2424 (62.80%), with a prevalence of HBsAg of 59 (2.85%) and 95 (4%), respectively. With irregular use of condoms during sexual intercourse, 1591 (78.22%) of these 63 (3.95%) were HBsAg positive. The study showed a population with poor socioeconomic profile; an intermediate prevalence for HBsAg serologic marker, differing from the results of the National Survey on Brazilian capital. It also revealed participants with use of sharps and low adherence to the use of condoms during sexual intercourse, suggesting that this is one of the biggest risk factors for acquisition of HBsAg in this study, since sexual transmission is typical from regions moderately endemic. As a contribution, it is suggested that the necessary deployment / implementation of action strategies for prevention and control of viral hepatitis, such as advice about containment measures, among them the safe sexual activity and the forbiddance of sharing pliers and razors, as well as immunization for hepatitis B.